Student workbook (Classroom version 3) (Harrisonburg, VA, 2010)
Contents exercises to help enhance a student's learning experience. The activities in this workbook provide an opportunity for learners to practice their language skills through reading and writing exercises that reinforce the concepts covered in the Rosetta Stone software.
Keywords: English language,Tiếng Anh; Study and teaching,Dạy và học